2002
DOI: 10.1002/jnr.10351
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of 12633 genes in Alzheimer hippocampal CA1: Transcription and neurotrophic factor down‐regulation and up‐regulation of apoptotic and pro‐inflammatory signaling

Abstract: Alterations in transcription, RNA editing, translation, protein processing, and clearance are a consistent feature of Alzheimer's disease (AD) brain. To extend our initial study (Alzheimer Reports [2000] 3:161‐167), RNA samples isolated from control and AD hippocampal cornu ammonis 1 (CA1) were analyzed for 12633 gene and expressed sequence tag (EST) expression levels using DNA microarrays (HG‐U95Av2 Genechips; Affymetrix, Santa Clara, CA). Hippocampal CA1 tissues were carefully selected from several hundred p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
426
1
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(453 citation statements)
references
References 75 publications
22
426
1
4
Order By: Relevance
“…However, since it has been shown that under certain circumstances some specific mRNA species are preferentially degraded (Barrachina et al, 2006;Buesa et al, 2004), it is advisable to verify individual mRNA integrity within an experiment. Our finding that RIN is the optimal marker for representing quality agrees with previously published studies that found RNA quality measures in assessing gene expression analysis (Colangelo et al, 2002;Jones et al, 2006;Ross et al, 1992). pH appears to be a good marker of peri-mortem tissue quality, but does not appear to be sensitive to freezer degradation, as shown in our tissue-thaw illustration.…”
Section: Discussionsupporting
confidence: 92%
“…However, since it has been shown that under certain circumstances some specific mRNA species are preferentially degraded (Barrachina et al, 2006;Buesa et al, 2004), it is advisable to verify individual mRNA integrity within an experiment. Our finding that RIN is the optimal marker for representing quality agrees with previously published studies that found RNA quality measures in assessing gene expression analysis (Colangelo et al, 2002;Jones et al, 2006;Ross et al, 1992). pH appears to be a good marker of peri-mortem tissue quality, but does not appear to be sensitive to freezer degradation, as shown in our tissue-thaw illustration.…”
Section: Discussionsupporting
confidence: 92%
“…23,24 However, although promising, the clear difficulties in obtaining brain tissue and the fragile nature of isolated RNA render transcriptome studies quite difficult. 25,26 Microarray analysis, widely used for ND and neuropsychiatric disorders, provided much information about the transcriptional profiles in pathological states, [27][28][29] although discordant results have been often reported. The lack of convergence could be attributed to microarray drawbacks (discussed in 8,9,15 ), as well as to the variable quality/integrity of RNAs strictly influenced by pH, 25 which may dramatically alter the binding to the nucleotide probes, affecting the measure of gene expression levels.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies using this technique have already been reported examining the changes in AD patients with mild to moderate disease [2][3][4][5]. In one such study, the gene expression differences between AD samples and control tissues utilized pooled RNA from 5 patients and demonstrated differences in the expression of genes associated with amino acid metabolism and neurotransmitter release [3].…”
Section: Introductionmentioning
confidence: 99%
“…In one such study, the gene expression differences between AD samples and control tissues utilized pooled RNA from 5 patients and demonstrated differences in the expression of genes associated with amino acid metabolism and neurotransmitter release [3]. Similarly, using pooled RNA preparations, Colangelo and colleagues specifically examined the hippocampal cornu ammonis 1 and demonstrated a very general overall repression of transcription in this region in AD patients [5]. In a third study, gene expression differences were observed between the affected hippocampus to that of the unaffected parietal cortex of the same patient [4].…”
Section: Introductionmentioning
confidence: 99%